Characteristics and Microbiome Profiling of Korean Gochang Bokbunja Vinegar by the Fermentation Process - Hoonhee Seo; Saebim Lee; Hyuna Park; Sujin Jo; Sukyung Kim; Md Abdur Rahim; Asad Ul-Haq; Indrajeet Barman; Youngkyoung Lee; Ayoung Seo; Mijung Kim; Il-yun Jung; et al. (Foods, 2022)
As NGS (next-generation sequencing) technology develops, metagenomics-based microbial ecology, that is, microbiome research, has recently led to the science of fermented food. Based on the above technology, a study was conducted to understand the characteristics of vinegar made from bokbunja, a local crop in Gochang-gun, Korea. Physicochemical characteristics of vinegar, organic acid analysis, microbial community analysis, and electronic tongue analysis were explored while fermenting the vinegar for 70 days under eight fermentation conditions according to the concentration of bokbunja liquid (100% or 50%), type of fermenter (porcelain jar or stainless container), and fermentation environment (natural outdoor conditions or temperature/oxygen controlled). As a result, distinct microbial community patterns were found in the stage of acetic acid fermentation and, accordingly, this fermentation of Gochang vinegar is classified into three categories. Vinegar prepared by the traditional method of outdoor fermentation using jars showed characteristics of “Acetobacter (42.1%)/Lactobacillus (56.9%) fusion fermentation”. Under conditions where oxygen and temperature were controlled indoors using jars, characteristics of “Komagataeibacter (90.2%) fermentation” were found. “Lactobacillus (92.2%) fermentation” characteristics were discovered under natural outdoor conditions using stainless steel containers. These fermentation pattern differences were related to taxonomic phylogenetic diversity, which was also considered involved in determining organic acid production and taste. These results will be helpful as a scientific basis for understanding the fermentation characteristics of Gochang vinegar and developing high-value-added traditional vinegar products.